A formação do homem no contexto histórico da crise ambiental: A consciência ecológica frente ao pensamento reducionista - de Sousa, Maria Celeste; Barbosa de Sousa, Albertino Sérvulo (Kairós: Revista Acadêmica da Prainha, 2021)
The objective and the relevance of this research is to demonstrate that the education of man in the context of the ecological crisis must be grounded in ecoespirituality, because only from this principle is it possible for an environmental education that visa an ecological awareness that does not ignore the integrity of the relationship between man and nature, opposing thus the hegemonic education based on anthropocentrism and ecocentrism, which are reductionist thoughts, since they deny the spiritual dimension of nature. In the first exhibit we argument about the anthropocentrism conception that instrumentalizes nature, that is, that conceives man as the only source of value of everything that exists. The second part is on the human formation founded on ecocentrism and the disagreement over the use of technology. Finally, the debate about the ecoespirituality, that is, the human formation founded on dialogue with the objective of rescuing the spiritual origin of the relationship between the man and nature, the only one capable of promoting an ecological ethics.